An overview of analgesics: opioids, tramadol, and tapentadol (Part 2) - R. van Rensburg; H. Reuter (South African Family Practice)
Pain can be caused by several mechanisms, and the development of chronic pain (also known as pain chronification) is a complex and often unpredictable process. Opioids, tramadol, and tapentadol provide pharmacological solutions to chronic pain of cancer or non-cancer origins, particularly if central sensitization is present. It may also be indicated for short-term use in acute pain. Despite large studies and meta-analyses of opioids for a variety of pain conditions, the evidence for its clinical effectiveness is still unclear. This is, however, mostly due to significant heterogeneity and bias between studies assessed. The dual analgesic mechanisms of tramadol and tapentadol appear to be effective options for pain relief, with an overall lower incidence of opioid-related adverse effects. Tapentadol has an analgesic effect comparable to the strong opioids, which appears to be mediated by its greater mu opioid receptor activity and more selective noradrenaline reuptake inhibition. Tramadol produces less analgesia than tapentadol, but it is also associated with reduced opioid-related adverse effects and dependence. The opioids and tramadol may be significantly affected by polymorphisms of CYP2D6, while this effect is lessened with tapentadol.